Effect of Ranitidine on the Pharmacokinetic and Pharmacodynamic Profile of Metformin in Rabbits - Rajendra, Dr. S. V. (Asian Journal of Pharmaceutics (AJP), 2023)
Background: The aim of this study was to investigate the effect of ranitidine, an H2-receptor antagonist, on the pharmacokinetics of metformin, a widely used antidiabetic drug in albino rabbits. Methods: Albino rabbits were divided into 3 groups, group I received metformin alone, group II received ranitidine alone, and group III received ranitidine 30 minutes prior to metformin. Blood samples were collected at various intervals post-administration for the estimation of blood glucose levels and metformin concentration. Results: The study found that the plasma metformin concentrations (CMet) were below the limit of quantification at 8 hours in group I, indicating a near complete elimination of the drug from systemic circulation. However, quantifiable levels of metformin were observed at 8 hours in group III, suggesting a significant increase in the mean residence time of the molecule caused by a decrease in metformin elimination. The study also found that the area under the curve of metformin was significantly increased by ranitidine pre-treatment in group III, suggesting an increase in systemic exposure to metformin. Conclusion: This study suggests that concomitant administration of ranitidine and metformin in rabbits leads to an increase in the mean residence time of metformin due to the inhibition of the organic cation transporter 1 by ranitidine, resulting in an increase in systemic exposure to metformin. The study highlights the potential for drug-drug interactions between ranitidine and metformin, which may impact the efficacy and safety of metformin treatment. Further studies in humans are needed to confirm these findings.